Food Security and Nutritional Status among Rural Poor: Evaluating the Impact of Rural Livelihood Mission in Odisha, India - Mishra, Abhisek; Mishra, Sujit Kumar; Baitharu, Iswar; Das, Tushar Kanti (Journal of Reviews on Global Economics, 2020)
This paper empirically examines the effect of participation in National Rural Livelihood Mission (NRLM) on the food security of rural poor. In parallel, it also introspects the nutritional profiles of the respondents. Data were collected from 220 respondents (including both beneficiaries and non-beneficiaries) through a structured questionnaire from Sonepur district of Odisha (India). For assessing the nutritional profile, the study uses 24 hour recall and food frequency questionnaire methods to collect the information on food consumption. Then food items were converted into their equivalent calories. A food security index (FSI) was constructed to capture the food security taking the average calories of food consumed by the respondents. The study finds a better food consumption pattern among beneficiaries than the non-beneficiaries. Further, the impact of NRLM is examined using randomised control trial method and finds a positive impact of the programme on the food security. That means, participation in the programme helps the beneficiaries to attain food security. Therefore, participation should be encouraged to mitigate the food insecurity problem.